EDUKASI PENCEGAHAN DAN PENGELOLAAN ASAM URAT MELALUI POLA MAKAN DAN GAYA HIDUP SEHAT PADA MASYARAKAT - Adinugraha Amarullah; Ivan Charles Seran Klau; Yani Ambari Yani Ambari; Herni Setyawati Herni Setyawati; Bella Fevi Aristia; Yohanes Ardian Kapri Negara (Jurnal Abdi Masyarakat Kita, 2026)
Abstract : Gout is one of the non-communicable diseases commonly found in the community and is closely associated with dietary patterns and lifestyle. Limited public knowledge regarding risk factors and preventive measures contributes to suboptimal gout management. This community service activity aimed to improve community knowledge on the prevention and management of gout through education on healthy dietary patterns and lifestyle modification. The activity employed a one-group design with health education delivered through interactive lectures, discussions, and educational media, conducted in the Tenggilis Mejoyo area, Surabaya. Knowledge evaluation was carried out using pretest and posttest questionnaires consisting of ten questions assessing understanding of gout, risk factors, high-purine foods, and the role of diet and lifestyle in gout prevention. The results showed an improvement in participants’ knowledge after the educational intervention. Prior to the activity, most participants had low (56.3 percent) and moderate (34.4 percent) knowledge levels; following the intervention, the proportion of participants with low knowledge decreased to 18.8 percent, while moderate and good knowledge levels increased to 53.1 percent and 28.1 percent, respectively. Participants also demonstrated better understanding of high-purine foods, the importance of physical activity, and sustainable gout management. In conclusion, community-based health education is effective as a promotive and preventive approach to improving public knowledge on gout prevention and management.